Kemampuan Metode Kombinasi Koagulasi Biji Asam Jawa Dan Filtrasi Akar Mangrove Dalam Menurunkan Kekeruhan Dan Kadar Klorida (Cl) Pada Air Sumur Gali Di Kawasan Pesisir - S, Syamsudin; Amin, Mulahizul (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
Clean water is a source of life for everyone, so its preservation and existence must be maintained as much as possible both in quantity and quality. Tamarind seeds (Tamarindus Indica L) can be used as an alternative coagulant to replace alum because it is more environmentally friendly. Mangrove roots are said to be able to reduce chloride levels because basically, like the roots of other higher plants, mangrove roots play a selective role in absorbing ions, which are carried and transported to the xylem. This study aims to determine the ability of a combination method of tamarind seed coagulation and mangrove root filtration in reducing turbidity and chloride (Cl) levels in dug well water in coastal areas. This type of research is quasi-experimental with coagulation and filtration methods. The results showed that in the initial sample the water turbidity was 76.9 NTU and the chloride content was 60,481.2 mg/l after processing using tamarind seeds, the turbidity reduction was 82.93% and the chloride level was 71.06%. Processing using mangrove roots resulted in a decrease in turbidity of 90.19% and chloride content of 90.51%. Meanwhile, the combination processing using tamarind seeds and mangrove roots resulted in a decrease in turbidity of 94.77% and chloride content of 96%. From the results of this study it can be concluded that the use of tamarind seeds and mangrove roots can reduce turbidity (NTU) and chloride (Cl) levels in dug well water in coastal areas with the ability to reduce turbidity by 94.77% and reduce chloride levels by 96%. The community can utilize tamarind seeds and mangrove roots in simple water treatment. Keywords : Clean Water; Tamarind Seed; Mangrove Roots